WTO disciplines on agricultural support: Experience to date and assessment of Doha proposals - Orden, David; Blandford, David; Josling, Timonthy; Brink, Lars (International Food Policy Research Institute, 2011)
When the World Trade Organization (WTO) was created in 1995, its members committed themselves to a set of disciplines for domestic support, market access, and export competition for agriculture. The Agreement on Agriculture laid the way for the pursuit of progressive reductions in world agricultural market distortions. Its supporters hoped the new rules and commitments would encourage countries to move domestic farm policies in a less trade-distorting direction. This research brief examines the Agreement's domestic support disciplines and their potential strengthening under the as-yet unfinished Doha Round negotiations. The brief provides a summary of the main conclusions from the March 2011 book WTO Disciplines on Agricultural Support: Seeking a Fair Basis for Trade. The analysis focuses on four developed countries (the United States, the European Union [as a single “country”], Japan, and Norway) and four developing countries (Brazil, China, India, and the Philippines). We highlight the substantial differences among these countries in their notifications of policy measures and the support they provide. Where a complete set of notifications is not available for 1995-2008, estimates (“shadow” notifications) are constructed. Domestic support is also projected through the mid-2010s and compared to existing and potential WTO commitments.